2020
DOI: 10.3126/jkahs.v3i2.30842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Supraclavicular and Infraclavicular Approach in Subclavian Vein Catheterization in Tertiary Center of Nepal

Abstract: Introduction: Central vein catheterization can be introduced in subclavian vein (SCV), internal jugular vein or femoral vein for volume resuscitation and invasive monitoring technique. Due to anatomical advantage and lesser risk of infection subclavian vein is preferred. Either supraclavicular (SC) or infraclavicular (IC) approach could be used for subclavian vein catheterization. The aim of the study was to compare SC and IC approach in ease of catheterization of SCV and record the complications present if an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…[ 3 , 5 , 7 , 20 , 22 - 30 ] Twelve studies reported haemothorax (NCT04637347),[ 3 , 5 - 7 , 20 - 23 , 27 , 29 , 30 ] ten reported haematomas (NCT04637347),[ 3 , 5 , 6 , 20 , 22 , 23 , 27 - 29 ] and three reported arrhythmias. [ 6 , 20 , 21 ] Two studies reported hydrothorax,[ 22 , 23 ] and two reported cardiac perforation/tamponade. [ 5 , 22 ] Kocum et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 , 5 , 7 , 20 , 22 - 30 ] Twelve studies reported haemothorax (NCT04637347),[ 3 , 5 - 7 , 20 - 23 , 27 , 29 , 30 ] ten reported haematomas (NCT04637347),[ 3 , 5 , 6 , 20 , 22 , 23 , 27 - 29 ] and three reported arrhythmias. [ 6 , 20 , 21 ] Two studies reported hydrothorax,[ 22 , 23 ] and two reported cardiac perforation/tamponade. [ 5 , 22 ] Kocum et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we included only RCTs and additionally included seven newly published RCTs unlike the previous systematic review (NCT04637347). [ 3 , 5 , 21 , 23 , 29 , 30 ] The sample size was approximately doubled from 1333 cases to 2482 cases. We demonstrated a robust evidence base for the SC approach using the GRADE approach.…”
Section: Discussionmentioning
confidence: 99%
“…Khapung et al has demonstrated a comparison between the SC and IC approaches and the mean access time in group SC catheterization was 2.12 ± 0.81 min compared to 2.83 ± 0.99 min in group IC (p-value=0.002). Furthermore, the first attempt at central venous catheterization was successful in 74.28% of the patients as compared with 57.14% in the IC group [35]. Similarly, Souadka et al exhibited that a long-term central venous access device for cancer chemotherapy can be performed more effectively with the SC approach [33].…”
Section: Figure 3: Surface Anatomy Of the Neck Indicating The Procedu...mentioning
confidence: 98%